Sistem Pendukung Keputusan Pemilihan Karyawan Teladan Menggunakan Metode Simple Multi-Attribute Rating Technique - M. Najib Dwi Satria; Very Hendra Saputra (CV. Keranjang Teknologi Media, 2023)
The selection of exemplary employees is a crucial stage in building a productive and high-performing team. The criteria for assigning exemplary employees involve a number of important factors, including dedication to the job, communication skills, integrity, and willingness to continue learning and improving. This study aims to recommend exemplary employees to companies by applying a decision support system model using the SMART method based on criteria namely experience, communication, length of work, responsibilities and abilities. The ranking results of exemplary employees using the SMART method recommend Rank 1 with a final value of 0.6729 obtained by Nurdin, Rank 1 with a final value of 0.636 obtained by Jonni, Rank 3 with a final value of 0.58802 obtained by Ahmad, Rank 4 with a final value of 0.2505 obtained by Galih, Rank 5 with a final value of 0.24636 obtained by Santoso.